Estimation of pharmacokinetic parameters of alpha-lipoic acid in the chicks model - Marwa R. Abdulghani; Ahmed S. Naser (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and objective: Alpha-lipoic acid is a drug used to treat diabetic neuropathy, and it has other uses as a dietary supplement. The target of the study was to investigate the concentration of therapeutic doses of Alpha-lipoic acid in the blood plasma of broiler chicks to define the pharmacokinetic parameters.